An investigation with teachers in initial training on: sequence of lucas and the numbers of k-Lucas (Research, Society and Development, 2019)
This work consists of exposing results on the sequence of Lucas and the numbers of k-Lucas as well as the contributions of the French mathematician Édouard Anatole Lucas from a study carried out with students of the discipline of the history of mathematics of the licentiate course in mathematics of the Institute Federal Education Science and Technology of the State of Ceará -IFCE. In order to identify and explore some specific properties of Lucas k-number, the teaching methodology used in the meetings was the didactic situations theory (TSD) and as a research methodology the didactic engineering (ED) phases. The data collected present some properties, as well as mathematical definitions developed by the initial training teachers participating in the study, which added in their professional practices a historical knowledge.